Influence of Prestraining on Tangent Modulus of Tubular Struts - Seyed M.R. Mortazavi (Fanāvarī-i āmūzish, 2006)
Strain reversal in the inelastic range may cause a dramatic drop in the tangent modulus for mild steel struts. Other material properties also affect the tangent modulus. Consequently the influence of several of these properties is examined for an electric-resistance welded steel tube. The variables chosen are: (1) Strain hardening caused by varying the amount of tensile prestrain; (2) strain aging; (3) and the Bauschinger effect, for a specific steel type. The results of 39 stub column tests on semi-killed steel specimens show that tensile prestrain reduces the tangent modulus compared with that found for the as-received tube, but strain aging is seen to be significant in reducing this loss in value. The variations obtained for the tangent modulus are illustrated. The variations are given as functions of the amount of tensile prestrain and whether the steel is fully aged or non-aged. The importance of knowledge of prior strain history of a material is highlighted.